Інтраопераційна диференційна діагностика солітарного вузла щитоподібної залози в хірургічному лікуванні - Брилинський, О. Р. (Clinical Endocrinology and Endocrine Surgery, 2008)
Results of intraoperative methods in diagnosis of uninodular pathology of the thyroid have been reported in the present work. These patients were treated surgically within the period of 2005-2007 in Lviv regional clinical hospital. Patients with uninodular goiter can be qualified to radical surgical treatment (thyroidectomy), first of all at the case of malignancy, or to resective methods (hemithyroidectomy) at the case of benign pathology. Using all spectrum of clinical, instrumental and laboratory methods of diagnosis, frequently occur difficulties of preoperative differential diagnosis of solitar nodule of the thyroid. Due to preoperative misdiagnosis there is a risk of performing inadequate surgical treatment, both at the case of malignancy or benign pathology. Results of intraoperative diagnosis were compared to final histologocal findings. Intraoperative histological study (frozen-section) admitted as the most appropriate method of diagnosis: sensitivity — 81,25%, specifity — 98,97%, diagnostic accuracy — 96,46%. Due to providing intraoperative methods of diagnosis the rate of adequate surgical treatment of uninodular goiter ranged to 98,23%. Thus, cytological and histological intraoperative methods of diagnosis should be used routinely during surgical treatment of patients, suffering at uninodular goiter.